Islam at 250 : Studies in Memory of G.H.A. Juynboll - Adang, Camilla,; Sijpesteijn, Petra M., (Leiden Studies in Islam and Society ;, 2020)
Islam at 250: Studies in Memory of G.H.A. Juynboll is a collection of original articles on the state of Islamic sciences and Arabic culture in the early phases of their crystallization. It covers a wide range of intellectual activity in the first three centuries of Islam, such as the study of ḥadīth , the Qurʾān, Arabic language and literature, and history. Individually and taken together, the articles provide important new insights and make an important contribution to scholarship on early Islam. The authors, whose work reflects an affinity with Juynboll's research interests, are all experts in their fields. Pointing to the importance of interdisciplinary approaches and signalling lacunae, their contributions show how scholarship has advanced since Juynboll's days.